Sosialisasi Proyek Penguatan Profil Pelajar Pancasila (P5) Sebagai Wujud dan Strategi Menciptakan Kehidupan yang Berkelanjutan di Era Modern - Yunus, Rusyda Nazhirah; Aji, Satriya Bayu; Harahap, Nursaima; Rumodhon, Berliansyah; Aswar, Luki (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2024)
This community service activity aims to socialize the concept of a sustainable lifestyle in Proyek Penguatan Profil PelajarPancasila (the project to improve the reinforcement value of Pancasila for students) by highlighting the importance of waste managementand planting trees. The activity was carried out to increase students' skills and awareness in managing organic waste as part of the effort to improve the reinforcement value of Pancasila, especially in terms of environmental issues. The approach includes several stages, which aresocialization of the importance of a sustainable lifestyle and the understanding of waste and plants. The results of this activity show an increase in students' awareness of the importance of waste management and planting trees as well as the implementation of a sustainable lifestyle. The data shows that students acquire an improved understanding of a sustainable lifestyle. Students are increasingly aware of themany things they can do to foster a sustainable lifestyle, which they can incorporate into their daily routines. This activity managed to contribute to improving the reinforcement value of Pancasila by grounding it in the context of environmental issues as well as enhancing students' practical skills in using everyday tools to minimize the damage to the environment to maintain a sustainable lifestyle.